Metabolical aspects associated with incorporation and clearance of uranium by broilers - Case study and a biophysical approach - Arruda-Neto, J. D.T.; Cestari, A. C.; Nogueira, G. P. [UNESP]; Fonseca, L. E.C. [UNESP]; Saiki, M.; Oliveira, E.; Manso-Guevara, M. V.; Vanin, V. R.; Deppman, A.; Mesa, J.; Garcia, F. (My University, 2005)
Groups of seven-day old Cobb broilers were fed with ration doped with uranyl nitrate at a fixed concentration (of 20 ppm), and two concentrations of phytase (120 and 180 ppm). Two animals per group were sacrificed weekly up to their adulthood. Calcium and uranium concentrations in tibia were measured by neutron activation analysis. It was observed that the biokinetics of U does not change by administration of phytase, but the U concentration in the bones increased ~ 40%, in average. Quite surprising too, the concentration of uranium (μg-U/g-bone) decreases all along the animal life period of 14-42 days, meaning that the skeleton mass is growing faster than the corresponding accumulation of uranium, while the concentration of calcium remains nearly constant, as expected. This last finding is interpreted as a possible interplay between two metabolical peculiarities, associated both with U transfer to (uptake), and U removed from (clearance) the bones, respectively. © Asian Network for Scientific Information, 2005.
Keywords: Bone; Cobb broiler; Metabolism; Phytase; Uranium uptake